The electromagnetic characteristics of the carbon-containing non-woven fabric with geometric irregularities - H. D. Abdulhadi; E. A. Almashat; N. M. Elsaiyah; O. V. Boiprav; A. M. Prudnik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of the study of electromagnetic characteristics of the carbon-containing non-woven fabric with geometric irregularities in the frequency range 0.7…17 GHz are presented.